Essential oil of Dracocephalum multicarle Montbr. & Auch (Labiatae) - F Mojab; A Rustaiyan; F Khalighi Sigaroodi (Institue of Medicinal Plants, ACECR, 2002)
The aerial parts of Dracocephalum multicaule Montbr. & Auch. (Fam. Labiatae) collected in August 1995 from Lasom Valley, Haraz Road, Province Tehran. The essential oil of the plant obtained by hydrodistillation (0.28%) by clevenger type apparatus and was analyzed by GC and GC/MS. 27 components were identified, constituing 90% of the oil, major component were limonene, -pinene and methyl geraniate.